(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
This article provides a comprehensive technique for incorporating Large Language Models (LLMs) into corporate employee engagement platforms, with an emphasis on technical design, implementation challenges, and longitudinal effect analysis. We examine sophisticated fine-tuning methods, such as bias mitigation strategies and privacy-preserving approaches, using proprietary HR datasets. The report emphasizes significant improvements in operational efficiency, with AI-powered HR solutions showing a 32% improvement in process optimization and 91.2% accuracy in employee feedback analysis across many languages. To address significant concerns about data privacy, scalability, and long-term efficacy, our system employs a multi-layered approach that incorporates federated learning implementations, differential privacy techniques, and robust security mechanisms. The implementation outcomes show notable benefits, including a 34% rise in employee satisfaction metrics and a 41% reduction in time-toinsight for HR analytics, while closely conforming to GDPR and CCPA laws.